2021
DOI: 10.18203/2320-6012.ijrms20212245
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polycystic ovarian syndrome on the mental health of women of reproductive age

Abstract: Polycystic ovary syndrome (PCOS) is defined as a hormonal disorder that is prevalent among women of reproductive age. It affects the metabolic, endocrine, and reproductive systems of the body as well as mental health. We compared up to 20 peer-reviewed literature that displayed the relationship between PCOS and mental health. We searched the PMC/NCBI/NIH database and we used the following keywords while searching the database: "polycystic ovarian syndrome" or "PCOS" and "mental health" or "depression" or "anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Polycystic ovary infertility accounts for the majority of infertility causes [ 8 ]. Adebisi O. et al believed that at the present stage, patients in the treatment group were 26–34 years old, with an average age of (25.2 ± 3.2) years; menstruation lasted from 1 to 7 months, with a mean of (2.54 ± 1.25) months; control patients were 24–35 years old, with a mean age of (64.2 ± 3.2) years; menstrual cycles ranged from 1 to 6 months, with an average menstrual cycle of (4.25 ± 1.25) months [ 9 ]. Almeshari W. et al believed that the main symptoms and signs of the laboratory examination results of B-ultrasonography in the symptoms related to sparse ovulation or anovulation; the late menstruation is up to 501 cases, accounting for 96.72%; 171 cases (33.1%) suffered from infertility, 157 were amenorrhea cases (30.31%), and there were 52 cases (10.04) of irregular vaginal bleeding [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Polycystic ovary infertility accounts for the majority of infertility causes [ 8 ]. Adebisi O. et al believed that at the present stage, patients in the treatment group were 26–34 years old, with an average age of (25.2 ± 3.2) years; menstruation lasted from 1 to 7 months, with a mean of (2.54 ± 1.25) months; control patients were 24–35 years old, with a mean age of (64.2 ± 3.2) years; menstrual cycles ranged from 1 to 6 months, with an average menstrual cycle of (4.25 ± 1.25) months [ 9 ]. Almeshari W. et al believed that the main symptoms and signs of the laboratory examination results of B-ultrasonography in the symptoms related to sparse ovulation or anovulation; the late menstruation is up to 501 cases, accounting for 96.72%; 171 cases (33.1%) suffered from infertility, 157 were amenorrhea cases (30.31%), and there were 52 cases (10.04) of irregular vaginal bleeding [ 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, the frequency of depression symptoms was found to be significantly higher in participants who complained of hirsutism ( p = 0.008) (Table 2). PCOS causes anovulatory cycle, hirsutism, acne, obesity, infertility, sleep problems, sexual problems, and mental problems associated with increased androgen levels (Adebisi et al, 2021). As revealed in our study, obesity was another factor affecting quality of life in women with PCOS ( p = 0.007) (Table 3).…”
Section: Discussionmentioning
confidence: 99%